Visionary in Arabic poetry (Journal of the College of Basic Education, 2022)
In the poetic heritage of the Arabs, there are many shining examples of the clash of poets and the rulers of political, social and religious power. It should not have specific ceilings, and as for those in power, they thought that raising the whip high in the faces of the violators, or opening the prison doors for them would be a successful method of silencing and gagging mouths. An explanation of this is what we find in many pre-Islamic, Islamic, Umayyad, Abbasid and modern poems, to the point that rejection is almost apparent in the course of our poetry and poets.